ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING - Santoso, Gunarto Heru (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2011)
This study aims to determine: 1) the influence of service quality dimensions in terms of tangibles, reliability, responsiveness, assurance and emphaty of trust, 2) the influence of trust on customer satisfaction, 3) the influence of service quality dimensions in terms of tangibles, reliability, responsiveness, assurance and trust toward customer satisfaction with trust as an intervening variable. This research was conducted at PT. Bank Rakyat Indonesia (Persero) Tbk Branch Wonogiri using a sample of 270 lenders. Sample method with convenience sampling method. Data collection techniques using questionnaires and documentation, while the data analysis methods used are research instruments include test validity and reliability testing; classical assumption include heteroscedasticity test, autocorrelation test, test for normality and multicollinearity test; hypothesis testing methods include path analysis, t test , F test, analysis of coefficient of determination (R2) as well as direct and indirect influence. The results showed that: 1) responsiveness and emphaty positive effect on customer trust. Reliability negatively on effect toward customer trust. Tangibles and assurance has not effect on customer trust, 2) emphaty and trust has positive influence on customer satisfaction, while tangibles, reliability, responsiveness and assurance not significant impact on customer satisfaction, 3) the trust our customers are able to mediate the influence of tangibles, reliability, responsiveness, assurance and emphaty of customer satisfaction so that the effect of tangibles, reliability, responsiveness, assurance and emphaty toward customer satisfaction can through customer trust.